2006
DOI: 10.4161/hv.2.2.2620
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical and Clinical Safety Studies on DNA Vaccines

Abstract: DNA vaccines are based on the transfer of genetic material, encoding an antigen, to the cells of the vaccine recipient. Despite high expectations of DNA vaccines as a result of promising preclinical data their clinical utility remains unproven. However, much data is gathered in preclinical and clinical studies about the safety of DNA vaccines. Here we review current knowledge about the safety of DNA vaccines. Safety concerns of DNA vaccines relate to genetic, immunologic, toxic, and environmental effects. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
66
0
4

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(70 citation statements)
references
References 76 publications
(120 reference statements)
0
66
0
4
Order By: Relevance
“…5,6 In addition to the differences in experimental system and to the generally immunosuppressed state of advanced cancer patients, our contrasting results may also reflect the greater difficulty in achieving robust immune responses with DNA vaccination in large animals when compared to rodents. [17][18][19] We chose to evaluate three established markers of immune activation and vaccine effectiveness, namely serum IgG levels, IFN-g production and lymphocyte proliferation. We also evaluated IL-10 production, given the evidence that this cytokine may be produced in response to Hsp65, 20 and may negatively affect immunization.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 In addition to the differences in experimental system and to the generally immunosuppressed state of advanced cancer patients, our contrasting results may also reflect the greater difficulty in achieving robust immune responses with DNA vaccination in large animals when compared to rodents. [17][18][19] We chose to evaluate three established markers of immune activation and vaccine effectiveness, namely serum IgG levels, IFN-g production and lymphocyte proliferation. We also evaluated IL-10 production, given the evidence that this cytokine may be produced in response to Hsp65, 20 and may negatively affect immunization.…”
Section: Discussionmentioning
confidence: 99%
“…DNA vaccines have been widely used in laboratory animals to elicit comprehensive humoral and cellular immune responses. Clinical trials have shown that DNA vaccines are safe and well tolerated [15,23] . Moreover, some reports have demonstrated that DNA vaccine could produce long-lasting immunity [24][25] .…”
Section: Discussionmentioning
confidence: 99%
“…However, their use in humans is hampered by extremely high toxicity of mucosal adjuvants [12,13] . Recently, DNA vaccine without such mucosal adjuvants has been demonstrated to induce both humoral and cellular immunity and is becoming a promising treatment for viral, bacterial and parasitic pathogens [14,15] . Protective immunity against HIV, influenza virus, rabies virus, malaria and tuberculosis has been shown in animal models [16][17][18][19] .…”
Section: Introductionmentioning
confidence: 99%
“…For genetic effects, the bio-distribution, persistence, and integration into the host genome were considered, which may lead to activation of oncogenes, inactivation of tumor suppressor genes, or to vertical transmission (Schalk et al, 2006). Our previous results showed that most bacteria and plasmids had cleared 8 h after oral inoculation of inhibin DNA vaccine in mice, although the plasmid may proliferate in different tissues from days 1-4.…”
Section: Requirements For An Inhibin Dna Vaccinementioning
confidence: 99%